Determination of thermodynamic acidity constants and limiting ionic mobilities of weak electrolytes by capillary electrophoresis using a new free software AnglerFish - Malý, Michal; Boublík, Milan; Pocrnić, Marijana; Ansorge, Martin; Lorinčíková, Kateřina; Svobodová, Jana; Hruška, Vlastimil; Dubský, Pavel; Gaš, Bohuslav (Electrophoresis, 2020)
Thermodynamic acidity constants (acid or acid-base dissociation constants, sometimes called also as ionization constants) and limiting ionic mobilities (both of them at defined temperature, usually 25°C) are the fundamental physicochemical characteristics of a weak electrolyte, that is, weak acid or weak base or ampholyte. We introduce a novel method for determining the data of a weak electrolyte by the nonlinear regression of effective electrophoretic mobility versus buffer composition dependence when measured in a set of BGEs with various pH. To correct the experimental data for zero ionic strength we use the extended Debye-Hückel model and Onsager-Fuoss law with no simplifications. Contrary to contemporary approaches, the nonlinear regression is performed on limiting mobility data calculated by PeakMaster's correction engine, not on the raw experimental mobility data. Therefore, there is no requirement to perform all measurements at a constant ionic strength of the set of BGEs. We devised the computer program AnglerFish that performs the necessary calculations in a user-friendly fashion. All thermodynamic pKa values and limiting electrophoretic mobilities for arbitrarily charged substances having any number of ionic forms are calculated by one fit. The user input consists of the buffer composition of the set of BGEs and experimentally measured effective mobilities of the inspected weak electrolyte.
Keywords: termodynamika; osmolární koncentrace; algoritmy; Algorithms; Nonlinear Dynamics; koncentrace vodíkových iontů; nelineární dynamika; Capillary electrophoresis; elektroforéza kapilární; Osmolar Concentration; Thermodynamics; Dissociation constant; Hydrogen-Ion Concentration; Software; Nonlinear regression; elektrolyty; Electrolytes; Limiting mobility; software; Electrophoresis, Capillary